Placental Chorioangioma Diagnosis and Management - Sanhal, Cem Yaşar; Yücel, Aykan (Gynecology Obstetrics & Reproductive Medicine, 2016)
Placental chorioangioma constitutes major importance in perinatology practice, as being the most common type of placental tumors, and having the potential of devastating perinatal outcomes. In this review, we report the symptoms, diagnostic findings and recent temporary and definitive treatment choices in patients with chorioangioma.